Influencing factors of non-adherence to treatment in patients diagnosed with hypertension - Simões, Cristiane da Fonseca (2022)
Systemic arterial hypertension (SAH) is one of the main risk factors for cardiovascular mortality. Adherence to treatment is a challenge for public health. The objective of the study was to evaluate the main factors that lead to discontinuation of pharmacological treatment. We evaluated 100 hypertensive individuals of both sexes, aged over 30 years. They were divided into two groups; Group 1, composed of 77 individuals who adhered to pharmacological treatment, and Group 2, formed by 23 individuals who discontinued drug treatment for blood pressure control. The framingham cardiovascular score, individual profile questionnaire (NAHAS), morisky-green questionnaire, and sociodemographic questionnaire were applied in both groups. Chi-square and Fisher's exact test were used for significance analysis, and for statistical analysis, the statistical software EPI 6.0 and Graph Prima 5.0. It was found that the group of individuals who do not adhere to drug treatment present higher systolic and diastolic blood pressures than the group that adheres to treatment. It was possible to conclude that several factors have a direct influence on the adherence to pharmacological treatment and that lifestyle must be allied to medication.